Novel Acoustic Method Provides First Detailed Measurements of Sediment Concentration Structure Within Submarine Turbidity Currents. Issue 5 (14th May 2020) - Simmons, S. M.; Azpiroz‐Zabala, M.; Cartigny, M. J .B.; Clare, M. A.; Cooper, C.; Parsons, D. R.; Pope, E. L.; Sumner, E. J.; Talling, P. J.
Abstract: Turbidity currents transport prodigious volumes of sediment to the deep sea. But there are very few direct measurements from oceanic turbidity currents, ensuring they are poorly understood. Recent studies have used acoustic Doppler current profilers (ADCPs) to measure velocity profiles of turbidity currents. However, there were no detailed measurements of sediment concentration, which is a critical parameter because it provides the driving force and debate centers on whether flows are dilute or dense. Here we provide the most detailed measurements yet of sediment concentration in turbidity currents via a new method using dual‐frequency acoustic backscatter ADCP data. Backscatter intensity depends on size and concentration of sediment, and we disentangle these effects. This approach is used to document the internal structure of turbidity currents in Congo Canyon. Flow duration is bimodal, and some flows last for 5–10 days. All flows are mainly dilute (<10 g/L), although faster flows contain a short‐lived initial period of coarser‐grained or higher‐concentration flow within a few meters of the bed. The body of these flows tends toward a maximum speed of 0.8–1 m/s, which may indicate an equilibrium in which flow speeds suspend available sediment. Average sediment concentration and flow thickness determine the gravitational driving force, which we then compared to average velocities. This comparison suggests surprisingly low friction values, comparable to or less than those of major rivers. This new approach therefore provides fundamental insights into one of the major sediment transport processes on Earth. Plain Language Summary: Seafloor‐hugging flows of sediment‐laden water, called turbidity currents, transport large volumes of sediment to the deep sea and pose a hazard to seafloor infrastructure such as pipelines and telecommunication cables. However, these flows remain poorly understood because of the limited field data available and the difficulty of measuring sediment concentration. It is sediment concentration that drives the flows, and this information is critical to modelers who seek to understand how fast and how far the flows are capable of running out along the seafloor. Recent field studies of turbidity currents have used acoustic flow meters that measure flow velocity through vertical profiles above the seabed. These instruments also record the magnitude of the sound reflected by the moving particles within the flow. This magnitude is related to both the concentration and grain size of the sediment. We take this information and determine the sediment concentration of 10 flows at 2, 000 m water depth in the Congo Canyon, offshore West Africa. Our results indicate that sediment concentrations are very dilute in most of the flow. We show how the retarding force of friction is lower than expected, meaning that current flow models are likely to underestimate how fast and far the flows runout. Key Points: First high‐resolution measurements of the sediment concentration and velocity structure for multiple oceanic turbidity currents are presented Flow duration and sediment volume are strongly bimodal, and some flows are sustained for 5–10 days All flows are mainly dilute (<10 g/L), but some flows have brief ( 15 min) initial period of coarser‐grained or denser flow near the bed